(3ebGdI aj GdOZOZIs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3bhd dMfjf Hf ESMGb ai GdSHH GdPi EPG CeQJ GdjO Ydi ehGVY ef GdHOf YQV ai Pdc GdehVY OZOZI eYgG VMc hHcGA eYkG bGd Ef LGdjfhS jbhd Ef GdbhI GdMjhGfjI ef GdfahS s
(3BNQgG (B:s
(3hdPdc deG cGf gPG GdehVY ef GdbOe cKjQ GdMS , hcGf eY Pdc djfkG cGf jYQV dg GdOZOZI EPG CeQJ GdjO Ydjg EfbVi Gdbhd ai GdOZOZI dMfjf Hf ESMGb hGdMeO ddg s
(3GfXQgG eY GdeQTO Qbe (B" 730"s
(3fSNI KGfjI ecQQI Yf GdSGHbIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B248 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs